Transition to IS project de-escalation: An exploration into management executive's influence tactics - PAN, Gary (Institutional Knowledge at Singapore Management University, 2011)
This paper seeks to understand the factors that shape management executives' influence behaviors and the influence tactics that may be utilized during de-escalation of commitment to information systems (IS) projects. De-escalation is potentially a more important issue than escalation because de-escalation provides remedies for the ills of escalation. Therefore, it is important to understand how project stakeholders' commitment to troubled IS projects may be transformed under management executives' influence, hence allowing project teams to carry out their de-escalation activities. Here, we adopt theories of leadership, politics, and interpersonal influence, as our lenses to examine the management executive's influence behaviors during the transition from escalation to de-escalation of a failing electronic procurement project at UK Borough Council. Based on the case analysis, we presented three key factors that shaped the influence behaviors and six influence tactics utilized separately or collectively by the management executive in the unfreezing, changing, and refreezing phases of project de-escalation. Through the findings, researchers may develop a deeper understanding of how project stakeholders may surrender previous failing courses of action and accept alternative courses of action. Practitioners may also devise useful influence tactics when de-escalating troubled IS projects.